The Development of Rafflesia Flower Ecotourism in Increasing the Income of the Mandailing Natal Regency Community - Nurintan Siregar; Enni Sari Siregar (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The development of the Rafflesia flower as an ecotourism object in Mandailing Natal has great potential to provide economic, social, and environmental benefits to the local community. The Rafflesia flower, known for its uniqueness and rarity, can become a major attraction for tourists interested in rare flora and biodiversity. This research explores the potential of Rafflesia flower ecotourism in Mandailing Natal, the factors influencing its success, and the management and conservation strategies needed to ensure its sustainability. The findings indicate that the development of Rafflesia flower ecotourism can increase local income, create jobs, and empower communities through active involvement in tourism management. In addition, conservation-based ecotourism can support the preservation of the natural habitat of the Rafflesia flower and raise environmental awareness. Tell However, there are several obstacles and challenges that must be addressed, including habitat limitations, lack of public awareness, limited funding and infrastructure, as well as the risks of climate change and natural disasters.